Inovasi Berbasis Lingkungan (Produk Ecoprint) Untuk Pemberdayaan Komunitas - Nuraini Eka Febriyanti; Munika Neni Berlian; Umi Setya Ramadhani; Nita Dita Puspitasari; Sari Wunikaresti; Ida Widaningrum (CV. Multi Kreasi Media, 2024)
The community partnership program aims to provide direct benefits to living communities in the social and economic fields as well as improving the quality of resources through empowering women from the PKK and Karang Taruna groups in Dukuh Buluerjo, Carangrejo Village, Sampung Ponorogo by utilizing natural materials found around their homes. It is hoped that this activity can solve the problems that exist in partner villages, namely the community's source of income is dominated by the agricultural sector, the village's natural potential has not been utilized properly, there is a lack of skills in managing village potential. The majority of Dukuh Bulurejo residents are house wives who have minimal income. The community partnership program consists of two activities, namely training in making ecoprints using natural materials in the environment around Dukuh Bluerjo and making audio-visual video son how to make ecoprints. It is hoped that the partnership program activities can be carried out continuously so that they can provide additional livelihoods for the local community because the selling value of ecoprint products is still quite high on the market.